2009
DOI: 10.1038/leu.2009.269
|View full text |Cite
|
Sign up to set email alerts
|

CD3+/CD19+-depleted grafts in HLA-matched allogeneic peripheral blood stem cell transplantation lead to early NK cell cytolytic responses and reduced inhibitory activity of NKG2A

Abstract: Natural killer (NK) cells have an important function in the antitumor response early after stem cell transplantation (SCT). As part of a prospective randomized phase III study, directly comparing the use of CD3 þ /CD19 þ -depleted peripheral blood stem cell (PBSC) harvests with CD34 þ -selected PBSC harvests in allogeneic human leukocyte antigen-matched SCT, we here show that the use of CD3 þ /CD19 þ -depleted PBSC grafts leads to early NK cell repopulation and reconstitution of the CD56 dim and CD56 bright NK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 39 publications
5
23
0
Order By: Relevance
“…These data confirmed previous research describing the abundant presence of CD56 bright NK cells in SLT [11,12]. In addition, we and others have shown that CD56 bright cells are the first mature NK cells to arise after allogeneic stem cell transplantation (SCT) [13,14]. Overall, these data support a model of in vivo human NK cell development in which CD34…”
Section: Cd3supporting
confidence: 80%
“…These data confirmed previous research describing the abundant presence of CD56 bright NK cells in SLT [11,12]. In addition, we and others have shown that CD56 bright cells are the first mature NK cells to arise after allogeneic stem cell transplantation (SCT) [13,14]. Overall, these data support a model of in vivo human NK cell development in which CD34…”
Section: Cd3supporting
confidence: 80%
“…Previously, Gentilini et al even showed a significant faster and sustained recovery of NK cells in a group of patients after RIC allogeneic SCT with CD3 + /CD19 + depleted grafts in comparison with patients with myeloablative allogeneic SCT with CD34 + selected grafts combined with adoptive NK cell infusion two days post SCT (Gentilini et al, 2007). Overall, these studies suggest that the use of NK cell rich grafts is favourable for the facilitation of fast and sustained NK cell recovery and differential reconstitution of the NK cell receptor repertoire, which may lead to improved donor NK cell alloreactivity in the GVL direction (Eissens et al, 2010a). Further prospective comparisons of the different graft manipulation methods for allogeneic SCT in the HLA-matched or haploidentical setting are warranted for more detailed analysis of the impact of graft composition on immune reconstitution.…”
Section: Infusion Of Mature Donor Nk Cells As Part Of the Graftmentioning
confidence: 99%
“…The use of enriched NK cell grafts for allogeneic SCT has shown to be beneficial for transplant outcome and provides enhanced GVL reactivity directly after transplantation as compared with conventional grafts that lack NK cells (Bethge et al, 2006;Eissens et al, 2010a;Kim et al, 2006). In addition, the head start in GVL reactivity may lead to better outcomes in terms of infectious events and overall survival after allogeneic SCT (Kim et al, 2005a).…”
Section: Allogeneic Sct Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…These results indicated that the early reconstituting NK cells after HSCT were mainly generated from the differentiation and maturation of NK precursors but not the expansion of mature NK cells in the graft. Nevertheless, the expansion of adoptive transferred NK cells also influences the reconstitution of donor NK cells since Eissens et al find that in HLA-matched allogeneic peripheral blood stem cell transplantation, CD3 + /CD19 + -depleted grafts which contain more mature NK cells than CD34 + -selected grafts lead to more rapid NK cell reconstitution [93]. + phenotype for at least 3-6 months [94].…”
Section: Donor Natural Killer Cell Reconstitution After Hematopoieticmentioning
confidence: 99%